Equivalent Circuit (EC) Approximation of Miniaturized Elliptical UWB Antenna for Imaging of Wood - Saeidi, T. (Springer, 2020)
Antenna can be considered as an essential section of a transceiver system which acts as a filter. This filter should produce a response from the transmitter to the receiver. The equivalent circuit (EC) of an elliptical patch UWB antenna is approximately modelled with an RLC equivalent circuit. The EC analysis helps to understand how a UWB antenna works, and how stubs (inductors) and notches affect the reflection coefficient result of a UWB antenna. Besides, a directly optimum of an antenna based on the EM simulation is very time-consuming, particularly, when the geometry of the antenna is complex. Hence, the research and analysis of the antennaâs EC model are imperative. After designing and analysis of the antennaâs EC, the impedance bandwidth result of both EC and the simulated prototype of antenna are compared. It depicts an acceptable agreement in terms of the resonances and the poles in the working BW. Â© Springer Nature Singapore Pte Ltd. 2020.